Optimization of enzymatic hydrolysis of tilapia muscle (Oreochromis niloticus) using response surface methodology (RSM) - Roslan, Jumardi; Mustapa Kamal, Siti Mazlina; Md. Yunos, Khairul Faezah; Abdullah, Norhafizah (Penerbit Universiti Kebangsaan Malaysia, 2014)
Fish protein hydrolysate was prepared from tilapia muscle using commercial Alcalase enzyme. Optimization of enzymatic hydrolysis process for preparing tilapia muscle protein hydrolysates (TMPH) was performed by employing central composite design (CCD) method of response surface methodology (RSM). O-phtaldialdehyde (OPA) method was employed to calculate the degree of hydrolysis (DH), which is the key parameter for monitoring the reaction of protein hydrolysis. The suggested model equation was proposed based on the effects of pH, temperature, substrate concentration and enzyme concentration on the DH. Optimum enzymatic hydrolysis conditions using Alcalase enzyme were obtained at pH7.5, temperature of 50oC, substrate concentration of 2.5% and enzyme concentration of 4.0%. Under these conditions, the highest value of the DH was achieved at 25.16% after hydrolysing at 120 min. The TMPH was further assessed for their nutritional value with respect to chemical and amino acid compositions. Molecular weight distributions of TMPH were characterized by SDS-PAGE. TMPH contains moderate amount of protein (28.14%) and good nutritive value with respect to the higher total amino acid composition (267.57 mg/g). Glutamic acid, aspartic acid and lysine were the most abundant amino acids present in TMPH with values 42.68, 29.16 and 26.21 mg/g, respectively. Protein hydrolysates from tilapia muscle containing a desirable peptide with low molecular weight which may potentially to be used as functional food products.